SOME ICONIC TEXTILE CRAFT OF HAND BLOCK PRINTS IN INDIA - Pandey, Anjali (International Journal of Research -GRANTHAALAYAH, 2022)
In India the practice of block- printing goes back to the ancient period. Near about 4000 years ago from the period of Indus valley civilization the Ajrakh of Kutch and Sindh uncovered the history. Ajrakh, Sanganer, Bagru, Kalamkari, and Bagh all have some specific specialities. Other places like Umedhpur, Tarapur are special for traditional prints using indigo.The other styles of hand-block printing are mostly in movement within the local area. The products made using this printing technique include saris, shawls, dress materials, dupattas, turban etc and furnishing material, usually bed sheets, curtains, table cloths, and pillow covers are used to print.Today for catching up with the youngsters, Shirts are also used to print in a new ethenic look.